REDESAIN STRATEGI PEMBELAJARAN PAI TINGKAT SMA: INTEGRASI ISU KONTEMPORER DAN ADAPTASI MEDIA DIGITAL (STUDI KASUS DI SMA IT ANNISA KADUNGORA) - Eep Saepuloh; Ganda Priatna Satmita; Gine Insan Permata; Yanti Julianti S; M. Tajudin Zuhri (As-Sulthan Journal of Education, 2026)
This study aims to analyze the development of adaptive learning strategies for Islamic Religious Education (PAI) at SMA IT Annisa Kadungora, Garut. High school PAI faces challenges due to gaps in students' religious understanding driven by diverse educational and family backgrounds. Using a descriptive qualitative method, data were gathered through interviews and questionnaires with educational practitioners. The results reveal that effective strategies integrate digital ethics as a core contemporary issue, implement Problem-Based Learning (PBL) to stimulate critical thinking, and utilize TikTok as a creative da'wah reference. Furthermore, a communicative approach using non-formal language creates a "safe space" for students in their identity-seeking phase. These findings suggest that pedagogical adaptation and digital integration are essential for maintaining the relevance of religious education in the Gen-Z era.